2008
DOI: 10.1038/ni.1663
|View full text |Cite|
|
Sign up to set email alerts
|

Interactions among the transcription factors Runx1, RORγt and Foxp3 regulate the differentiation of interleukin 17–producing T cells

Abstract: The molecular mechanisms underlying the differentiation of interleukin 17–producing T helper cells (TH-17 cells) are still poorly understood. Here we show that optimal transcription of the gene encoding interleukin 17 (Il17) required a 2-kilobase promoter and at least one conserved noncoding (enhancer) sequence, CNS-5. Both cis-regulatory elements contained regions that bound the transcription factors RORγt and Runx1. Runx1 influenced TH-17 differentiation by inducing RORγt expression and by binding to and act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
449
1
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 447 publications
(469 citation statements)
references
References 37 publications
(62 reference statements)
16
449
1
3
Order By: Relevance
“…Deficiency in ror-gt results in a major reduction in the number of Th17 cells and protection from experimental autoimmune encephalomyelitis; by corollary, over-expression of Ror-gt promotes Th17 development. Recently, it was shown that Ror-ad or Runx 1 can synergize with Ror-gt to promote IL-17 expression [27,28].…”
Section: Cd4mentioning
confidence: 99%
See 2 more Smart Citations
“…Deficiency in ror-gt results in a major reduction in the number of Th17 cells and protection from experimental autoimmune encephalomyelitis; by corollary, over-expression of Ror-gt promotes Th17 development. Recently, it was shown that Ror-ad or Runx 1 can synergize with Ror-gt to promote IL-17 expression [27,28].…”
Section: Cd4mentioning
confidence: 99%
“…Deficiency in ror-gt results in a major reduction in the number of Th17 cells and protection from experimental autoimmune encephalomyelitis; by corollary, over-expression of Ror-gt promotes Th17 development. Recently, it was shown that Ror-ad or Runx 1 can synergize with Ror-gt to promote IL-17 expression [27,28].Human Th17 cells express IL-17A, IL-17F, TNF-a, , as well as . Many groups have also examined the expression of chemokine and cytokine receptors on human Th17 cells [26,30,31,[34][35][36][37], with the overall conclusion that co-expression of CCR4, CCR6 and the IL-23R, but not CXCR3, is characteristic and best distinguishes Th17 cells from other human Th-cell subsets.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…T H 17 differentiation requires retinoid-related orphan receptor (ROR)-γt, a transcription factor that is induced by TGF-β in combination with IL-6, -21, and -23, all of which activate STAT3 phosphorylation (4). Additionally, various host proteins such as aryl hydrocarbon receptor (AHR) (5-7), Runt-related transcription factor 1 (Runx1) (8), Interferon regulatory factor 4 (IRF4) (9), and Basic leucine zipper transcription factor ATF-like (BATF) (10) positively regulate T H 17 differentiation, whereas B-cell lymphoma 6 (Bcl-6) (11,12), Ets-1 (13), Nuclear receptor subfamily 2 group F member 6 (NR2F6) (14), Peroxisome proliferatoractivated receptor gamma (PPAR-γ) (15), Suppressor of cytokine signaling 3 (SOCS3) (16), and Liver X receptor (LXR) (17) inhibit generation of T H 17 cells. However, very few studies have addressed the regulation of T H 17 differentiation by microRNAs, a topic that should be investigated further.…”
mentioning
confidence: 99%
“…77,107 Other transcription factors are also involved in the full differentiation of Th17 cells, including IFN regulatory factor 4 and runt-related transcription factor 1. 75,76 Further studies revealed that IL-23 is not required for Th17 differentiation, but can promote the growth, survival and effector function of this lineage.…”
Section: Cell Sources and Regulation Of Il-17mentioning
confidence: 99%